Analisis Proses Bisnis Gedung Yudhistira Manufacturing Area 1 PT Tirta Nvestama (AQUA) Pandaan Dengan Menggunakan Failure Mode And Effect Analysis (FMEA) - Aulia Aprilliana; Yusi Tyroni Mursityo; Aditya Rachmadi (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2019)
PT Tirta Investama (AQUA) Pandaan has several problems in the production process that occurred in 2017 and 2018. There are 4 problems in 2017 due to the negligence of work carried out by employees, and 1 problem caused because the work was not carried out according to the standards set. And in 2018 there were 3 problems caused by human negligence. Every problem is input into the Behavior Safety Analysis (BSA) system. The first step taken in this research is to model existing business processes using Business Process Model and Notation (BPMN). Furthermore, each activity contained in the business process is analyzed using the Failure Mode and Effect Analysis (FMEA) method so that the problems in each activity can be analyzed in depth. After obtaining the results of analysis using Failure Mode and Effect Analysis (FMEA), then look for the root cause of each activity using Root Cause Analysis (RCA). The use of RCA is expected to help companies in improving the production process so as to reduce existing problems. The results of this study are found to be the main factor causing problems during the production process, namely negligence of workers who do not comply with regulations. Because this is the main factor causing the problem, it is recommended to add features to the Behavior Safety Analysis (BSA) system. The added feature is the Person Involved feature, the number of negligence features, and the cause category features. So that the company is easy to carry out further evaluation on every problem that occurs and makes it easier to find out employees who often make mistakes.